Piggybacking Historic Architecture: Air Rights and the Subdivision of Space - David Karle (Anuari d’Arquitectura i Societat)
The once iconic centerpieces of our urban cores are being forgotten amidst the shadows of new construction, calling the life and death cycle of these landmark buildings into question. If a modernising city wishes to densify their land-poor cities they must look up and consider the air above existing buildings as buildable space. By reconsidering the untouched nostalgia inherent in our traditional notions of preservation, designers must challenge the use of airspace above landmark historic buildings. As culture, society, and our environment continually evolve, how do we preserve history while also bringing it into the future? This question can be answered by making contextually conscious use of valuable air space above historic buildings and is exemplified in a in a design research prototype for the 1904 Grand Manse in the state of Nebraska, USA, that applies architectural research methods while negotiating local zoning code in accordance with the demands of a growing city.